The Application of Article 56 Paragraph (1) of the Indonesian Criminal Procedure Code (KUHAP) from a Human Rights Perspective in Relation to the Integrated Criminal Justice System in Indonesia - Sepranadja (International Journal of Science and Society, 2024)
Law enforcement aims to promote societal order and legal certainty by clearly defining the roles, responsibilities, and authorities of the institutions tasked with upholding the law, in accordance with their respective jurisdictions. This process extends beyond the mere fulfillment of duties; it involves the comprehensive enforcement of legal norms. The law serves as a mechanism for safeguarding human interests, and to protect these interests effectively, it must be applied equitably. Upholding basic human rights is imperative, and no entity, including the state, has the right to infringe upon an individual's fundamental rights. The adoption of the Miranda Rule/Miranda Principles into Indonesian positive law—through the enactment of Law Number 39 of 1999 on Human Rights and Law Number 12 of 2005 on the Ratification of the International Covenant on Civil and Political Rights—has strengthened the rights of suspects and defendants, particularly their right to legal assistance and defense. The Miranda Rule/Miranda Principles are vital to the criminal justice system, particularly in protecting the rights of suspects during interrogation. As a legal state, Indonesia upholds these principles, which are integrated into various judicial laws. These principles emphasize the necessity for law enforcement officers to prioritize the rights of suspects and defendants. Providing legal assistance to suspects or defendants is a fundamental aspect of the criminal justice system, and it is expected that all law enforcement officers conduct their duties in a coordinated manner, adhering to the principles of this system. The presence of legal counsel, as mandated by Article 56 of the Indonesian Criminal Procedure Code (KUHAP), is essential; neglecting this requirement can result in the nullification of the proceedings' outcomes, including investigations, prosecutions, or trials.